Accuracy of owner-reported diagnoses for dogs enrolled in the Dog Aging Project as compared to veterinary electronic medical records - Sarah M. Schmid; Courtney L. Sexton; Alexandria Yoerger; Mandy Kauffman; Robyn L. McClelland; Kate E. Creevy; Audrey Ruple (PLoS ONE, 2026)
The objective of this project was to evaluate the accuracy of owner-reported health diagnoses in dogs compared to veterinary electronic medical records (VEMRs) using data from the Dog Aging Project (DAP), a longitudinal study of companion dogs in the United States. We hypothesized that owner-reported diagnoses would align more closely with VEMRs for acute or emergent conditions and less so for benign or self-limiting conditions. A subsample of 350 dogs was selected from the 2020 curated DAP dataset (n = 27,541). Dogs were included if they had VEMRs covering ≥ 85% of their life up to the time of survey completion. Forty-one dogs were excluded due to incomplete VEMRs, resulting in a final sample of 309 dogs included in this observational study comparing owner responses in the Health and Life Experience Survey (HLES) ( https://github.com/dogagingproject/dataRelease/tree/master/SurveyInstruments/HLES ) to VEMR data abstracted by masked reviewers. VEMR reviewers completed a survey mirroring HLES and identified supporting evidence for each diagnosis. Agreement between owner-reported and VEMR-verified diagnoses was assessed across 20 disease categories, with a focus on five target disease categories (TDCs). Agreement between owner and VEMR data was ≥ 90% in 10 of 20 disease categories. Agreement was highest in endocrine, immune, and “other” categories (99%) and lowest in dental/oral (44%). Among TDCs, orthopedic and traumatic conditions had higher agreement (>78%), while dermatologic and dental/oral categories showed the least. Owner-reported dog health data showed substantial concordance with VEMRs for many disease categories, supporting their utility in research. Thus, owner-reported diagnoses might provide a reliable and scalable supplement or alternative to VEMRs in veterinary research and epidemiology.